The Influence of Motivation and Work Environment on Organisational Citizenship Behavior of Health Workers RSAU Esnawan Antariksa Jakarta - Juhaeti, Juhaeti; Damayanti, Novita; Dyah Widyastuti , Dewi (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Organisational Citizenship Behavior (OCB) is the contribution of individuals who Exceeding the demands of roles in the workplace is one of the important factors in improve organizational performance that supports the proper functioning of the organization effective and efficient. OCB behavior of a health worker can show quality of service. This research is motivated by Motivation and the environment Work on Organisational Citizenship Behavior (OCB).at RSAU dr. Esnawan Space. Many ways have been done by the Hospital in order to improving the quality of services, including by providing services or service excellence. This research was conducted at RSAU dr. Esnawan Antariksa with the aim of To find out the influence of motivation and work environment on Organisational Citizenship Behavior (OCB). Data collection using a questionnaire with multiple linear regression data analysis.The results of this study show that (1) Work Motivation has an effect positive and partially significant to the Organisational Citizenship of Bihavior, (2) The Work Environment has a positive and significant effect on the Organizational Citizenship Bihavior, as well as Work Motivation and Work Environment have a positive and significant effect simultaneously on Organizational Citizenship Bihavior with a contribution of 57.6% while the remaining 42.4% explained by other variables that are not included in this study.